2021
DOI: 10.2147/ott.s315813
|View full text |Cite
|
Sign up to set email alerts
|

SQLE Mediates Metabolic Reprogramming to Promote LN Metastasis in Castration-Resistant Prostate Cancer

Abstract: Background: Almost all metastatic hormone-sensitive prostate cancers (mHSPC) will develop into metastatic castration-resistant prostate cancer (mCRPC) after androgen deprivation therapy (ADT). The expression level of squalene monooxygenase (SQLE) is increased in CRPC cells and regulates cholesterol metabolism. This study verified the biological function and mechanisms of SQLE in CRPC. Methods: The expression of SQLE in human prostate cancer cells was overexpressed or silenced and its efficacy on cell survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…High SQLE expression and gene amplification are associated with a poor prognosis in head and neck squamous cell carcinoma ( 39 ). SQLE was also shown to mediate metabolic reprogramming to promote metastasis in castration-resistant prostate cancer ( 40 ). To date, the role of SQLE has not been examined in OS.…”
Section: Discussionmentioning
confidence: 99%
“…High SQLE expression and gene amplification are associated with a poor prognosis in head and neck squamous cell carcinoma ( 39 ). SQLE was also shown to mediate metabolic reprogramming to promote metastasis in castration-resistant prostate cancer ( 40 ). To date, the role of SQLE has not been examined in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, studies have demonstrated that both cholesterol biosynthesis and efflux are reprogrammed in mCRPC, which may be major contributors to tumor growth and lethal progression [6][7][8]. Indeed, elevated expression of cholesterol biosynthesis rate-limiting enzymes such as SQLE have been strongly correlated with poor outcome of PCa [7,9,10]. Low or loss of expression of key efflux proteins such as ABCA1 and metabolic enzymes such as CYP27A1 are also associated with the disease progression [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol is a vital component in cell membranes and a precursor for steroid synthesis, including androgens. In prostate cancer, high cholesterol and cholesterol biosynthesis have been associated with for example progression [ 48 ], metastasis [ 49 ], and poor treatment response to taxanes [ 50 ]. Together with the downregulation of the cholesterol synthesis pathway by ostecoclasts in the present study, this would indicate a suppressive role of osteoclasts on aggressive features associated with cholesterol.…”
Section: Discussionmentioning
confidence: 99%